PERAN MODERASI PROFITABILITAS TERHADAP FAKTOR-FAKTOR YANG MEMPENGRUHI NILAI PERUSAHAAN - Galuh Tri Wahyuningsih; Mochlasin Mochlasin (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2021)
Abstract: This study aims to determine the effect of Islamic Social Reporting (ISR), firm size (SIZE), and capital structure (DER) on firm value (PBV) moderated by profitability (ROE). The sampling technique in this study used a purposive sampling technique. There are 13 samples of companies with a company population of 50 companies listed on the Jakarta Islamic Index (JII) in 2013-2019. The data analysis technique uses a quantitative approach. The conclusion from the results of this study is that partially ISR has a significant positive effect on firm value (PBV), firm size (SIZE) has a positive and insignificant effect on firm value (PBV), capital structure (DER) has a negative and insignificant effect on firm value ( PBV). The profitability variable is proven to be able to moderate the relationship between ISR, firm size, and capital structure to firm value. Meanwhile, the variables of ISR, firm size and capital structure have a positive and significant effect on firm value simultaneously. Keywords: ISR, SIZE, DER, ROE, PBV